2003
DOI: 10.1111/j.1365-2621.2003.tb09653.x
|View full text |Cite
|
Sign up to set email alerts
|

Mild‐Heat and High‐Pressure Inactivation of Carrot Pectin Methylesterase: A Kinetic Study

Abstract: Pectin methylesterase (PME) was extracted from carrots and purified by affinity chromatography. The thermal high-pressure inactivation of the PME was investigated in a model system. Under these conditions, the (thermo) stable fraction is not inactivated and the isobaric-isothermal inactivation followed a fractional-conversion model. At lower pressures (< 300 MPa) and higher temperatures (> 50 °C), an antagonistic effect of pressure and heat was observed. A 2nd-and 3rd-degree polynomial model (derived from avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 27 publications
3
63
1
2
Order By: Relevance
“…Another possible source of the high pressure stability may be the presence of ß-helices in amyloid fibrils. It is well known that enzymes that contain ß-helices are very pressure stable (59).…”
Section: Intermolecular Interactions Of Unfolded Proteinsmentioning
confidence: 99%
“…Another possible source of the high pressure stability may be the presence of ß-helices in amyloid fibrils. It is well known that enzymes that contain ß-helices are very pressure stable (59).…”
Section: Intermolecular Interactions Of Unfolded Proteinsmentioning
confidence: 99%
“…However, PME enzymes have been found that exhibit a wide thermal stability range in orange, acerola and carrot juices. This suggests the presence of thermostable and thermolabile fractions of PME isoenzyme complexes with irregular characteristics (Arbaisah et al, 1996;de Assis et al, 2000;Ly-Nguyen et al, 2003;Versteeg et al, 1980). In this regard, it should be noted that the technological problems in citrus juice associated with PME have been attributed to a high molecular weight thermostable fraction, which is also crucial in the establishment of pasteurization values in orange juice (Versteeg et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…La desnaturalización de enzimas por calor, suele a menudo ser irreversible debido a la ruptura de enlaces covalentes y/o la agregación de proteínas desdobladas (Ly-Nguyen et al, 2003;Puppo et al, 2004).…”
Section: Determinación De La Concentración De Proteínasunclassified